Combined Procedures with Laparoscopic Cholecystectomy - Savita, KS (Springer-Verlag, 2010)
With advancement in laparoscopic surgery a number of surgical procedures can be performed combined with laparoscopic cholecystectomy in a single surgery. We evaluate the safety & efficacy of such surgeries. A retrospective review of all patients who had undergone combined procedures with laparoscopic cholecystectomy during January 2005 to June 2009 was performed. 3144 laparoscopic cholecystectomies were performed in the period from January 2005 to June 2009. Of these, 401 cases were combined with another procedure. The mean operative time was 80 min (range 50–270 min). The mean hospital stay was 3.2 days (range 1–5 days). The mean no. of days injectable analgesics was required was 2 days (range 1 day–4 days). Combined procedures provide patients with all the benefits of minimal invasive surgery and also give the benefit of single time anaesthesia without adding to post operative morbidity & hospital stay.